Mucin adhesion of serial cystic fibrosis airways Pseudomonas aeruginosa isolates - Herrmann, Christian; Lingner, Meike; Herrmann, Susanne; Brockhausen, Inka; Tümmler, Burkhard (Frontiers in Cellular and Infection Microbiology, 2024)
The chronic airway infections with Pseudomonas aeruginosa are the major co-morbidity in people with cystic fibrosis (CF). Within CF lungs, P. aeruginosa persists in the conducting airways together with human mucins as the most abundant structural component of its microenvironment. We investigated the adhesion of 41 serial CF airway P. aeruginosa isolates to airway mucin preparations from CF sputa. Mucins and bacteria were retrieved from five modulator-naïve patients with advanced CF lung disease. The P. aeruginosa isolates from CF airways and non-CF reference strains showed a strain-specific signature in their adhesion to ovine, porcine and bovine submaxillary mucins and CF airway mucins ranging from no or low to moderate and strong binding. Serial CF clonal isolates and colony morphotypes from the same sputum sample were as heterogeneous in their affinity to mucin as representatives of other clones thus making ‘mucin binding’ one of the most variable intraclonal phenotypic traits of P. aeruginosa known to date. Most P. aeruginosa CF airway isolates did not adhere more strongly to CF airway mucins than to plastic surfaces. The strong binders, however, exhibited a strain-specific affinity gradient to O-glycans, CF airway and mammalian submaxillary mucins.